1977
DOI: 10.1111/j.1476-5381.1977.tb07550.x
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Prostaglandins in the Muscle of Human Isolated Small Intestine to Neurogenic Responses

Abstract: In strips cut parallel to the longitudinal or circular muscle, indomethacin (2‐10 μg/ml) usually lowered the tone, thus probably accounting for the reduction of nerve‐mediated relaxations to electrical field stimulation. In longitudinal muscle strips, indomethacin enhanced contractions which occurred during electrical stimulation, probably because tone fell, but antagonized after‐contractions. By contrast, in the circular muscle indomethacin reduced initial contractions but enhanced after‐contractions. Prostag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Previous reports showed that indomethacin reduced electrically induced after contractions in longitudinal muscle of human small intestine or mouse colon, 28 36 raising the interesting possibility that endogenous prostanoids contribute to facilitate the activity of excitatory non-cholinergic pathways. Although our study focused on the influence of cyclooxygenase isoforms on cholinergic motility, the present findings, together with previous studies, 28 29 36 indicate that the cyclooxygenase enzymes are involved in a complex regulatory network of intestinal neuromuscular functions, and that further investigations are required to clarify the relationships between cyclooxygenase isoforms and non-cholinergic enteric pathways. It also remains to be examined whether cyclooxygenase enzymes are expressed in interstitial cells of Cajal and/or regulate any activity of these cells at the human gut level.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Previous reports showed that indomethacin reduced electrically induced after contractions in longitudinal muscle of human small intestine or mouse colon, 28 36 raising the interesting possibility that endogenous prostanoids contribute to facilitate the activity of excitatory non-cholinergic pathways. Although our study focused on the influence of cyclooxygenase isoforms on cholinergic motility, the present findings, together with previous studies, 28 29 36 indicate that the cyclooxygenase enzymes are involved in a complex regulatory network of intestinal neuromuscular functions, and that further investigations are required to clarify the relationships between cyclooxygenase isoforms and non-cholinergic enteric pathways. It also remains to be examined whether cyclooxygenase enzymes are expressed in interstitial cells of Cajal and/or regulate any activity of these cells at the human gut level.…”
Section: Discussionsupporting
confidence: 47%
“…Furthermore, the enhancing effects of cyclooxygenase inhibitors are unlikely to depend on variations in muscle tone as no significant changes in resting tone were observed when incubating colonic preparations with SC-560, DFU or, in most cases, indomethacin. Although in a previous study indomethacin enhanced the contractile responses of human small intestine longitudinal muscle to electrical stimulation or acetylcholine, and such effects were proposed to result from concomitant reductions in muscle tone, 28 it should be acknowledged that the response patterns of intestinal muscle to cyclooxygenase products may vary considerably with the species, gut region, and muscle layer. Moreover, in line with our observations, indomethacin had no effect on basal tone but increased the response to acetylcholine when assayed on cat ileal smooth muscle.…”
Section: Discussionmentioning
confidence: 92%
“…Muscle cut adjacent to the esophagogastric junction relaxed in response to EFS whereas strips cut progressively more rostral showed a biphasic response, consisting of an after-contraction Burleigh 1979 Stomach Fundus and antrum, circular muscle: frequency-dependent, monophasic contractions, predominantly cholinergic but with simultaneous nitrergic inhibitory influence suppressing amplitude of contractions Bennett & Stockley 1975; Fundus and antrum, circular muscle: during EFS the nitrergic motor function activated more readily by EFS than the cholinergic system Pyloric sphincter: cholinergically mediated contraction mostly in the proximal region of the sphincter and a neuronally mediated inhibitory response mostly in the more distal region of the sphincter Tomita et al, 2007 Duodenum and terminal ileum Circular muscle preparations: nitrergically mediated relaxations usually occurred at lower frequencies of stimulation, with cholinergically mediated contractions at higher frequencies Bennett & Stockley, 1977;Maggi et al, 1990; Ascending or descending colon…”
Section: Response To Efs Referencesmentioning
confidence: 99%
“…In the urethral smooth muscles, controversy as to whether PGs, especially the PGE series, induce relax ations or no responses [4,14] has continued. The present examination clarified that smooth muscle preparations isolated from the proximal urethra of dogs showed relax ations in response to various doses of PGEt and PGE2, and contractions in response to PGF2a.…”
Section: Discussionmentioning
confidence: 99%
“…Many investiga tions have been performed on the actions of PGs in var ious organs [4][5][6], However, there are few experimental reports [7] in which the effects of PGs on the urinary tract have been observed. Therefore, the present study was designed to explore in detail the effects of PGs on smooth muscles isolated from canine urinary bladder and ure thra, and a possibility of using PGs for the treatment of incomplete bladder emptying was discussed.…”
Section: Introductionmentioning
confidence: 99%